The Role of Internet Usage in Shaping Psychological Well-Being : A Comparative Study of Internet-Addicted and Non-Addicted Undergraduates - Jasmine A.L, Yeap; Thurasamy, Ramayah; Hasliza, Abdul Halim; Noor Hazlina, Ahmad; Izzal Asnira, Zolkepli; Lo, May Chiun (University of Tehran, 2025)
This study explores the psychological impact of Internet addiction, comparing the functioning of Internet-addicted individuals to their non-addicted counterparts. A survey of 175 undergraduates from a Malaysian public university assessed their perceptions of 18 statements reflecting key facets of psychological well-being, including autonomy, environmental mastery, positive relationships, personal growth, purpose in life, and self-acceptance. Significant differences were observed in 14 out of 18 statements, with small to medium effect sizes, indicating meaningful disparities between the two groups. The findings suggest that Internet-addicted individuals are more likely to experience challenges in psychological well-being, often turning to the Internet as a coping mechanism for dissatisfaction or unhappiness. This study underscores the need for targeted interventions in the realm of information technology to promote healthier Internet use and address its psychological effects.